Variants Within TSC2 Exons 25 and 31 Are Very Unlikely to Cause Clinically Diagnosable Tuberous Sclerosis. Issue 4 (12th January 2016) - Ekong, Rosemary; Nellist, Mark; Hoogeveen‐Westerveld, Marianne; Wentink, Marjolein; Panzer, Jessica; Sparagana, Steven; Emmett, Warren; Dawson, Natalie L.; Malinge, Marie Claire; Nabbout, Rima; Carbonara, Caterina; Barberis, Marco; et al.
Abstract : Confirmed TSC‐causing mutations have been reported in all coding TSC2 exons except in the alternatively spliced exons 25 and 31. Evidence gathered from TSC2 RNA expression data, in vitro functional assays and conservation analysis indicate that variants within TSC2 exons 25 and 31 (truncating, in‐frame indelsand missensevariants reported so far) are unlikely to cause clinically diagnosable TSC. ABSTRACT: Inactivating mutations in TSC1 and TSC2 cause tuberous sclerosis complex (TSC). The 2012 international consensus meeting on TSC diagnosis and management agreed that the identification of a pathogenic TSC1 or TSC2 variant establishes a diagnosis of TSC, even in the absence of clinical signs. However, exons 25 and 31 of TSC2 are subject to alternative splicing. No variants causing clinically diagnosed TSC have been reported in these exons, raising the possibility that such variants would not cause TSC. We present truncating and in‐frame variants in exons 25 and 31 in three individuals unlikely to fulfil TSC diagnostic criteria and examine the importance of these exons in TSC using different approaches. Amino acid conservation analysis suggests significantly less conservation in these exons compared with the majority of TSC2 exons, and TSC2 expression data demonstrates that the majority of TSC2 transcripts lack exons 25 and/or 31 in many human adult tissues. In vitro assay of both exons shows that neither exon is essential for TSC complex function. Our evidence suggests that variants in TSC2 exons 25 or 31 are very unlikely to cause classical TSC, although a role for these exons in tissue/stage specific development cannot be excluded.